2011
DOI: 10.1161/circulationaha.110.983874
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis

Abstract: Background Observational studies suggest there are differences in adherence to antihypertensive medications in different classes. Our objective was to quantify the association between antihypertensive drug class and adherence in clinical settings. Methods and Results Studies were identified through a systematic search of English-language articles published from inception of computerized databases till February 1, 2009. Studies were included if they measured adherence to antihypertensives using medication ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
4
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(83 citation statements)
references
References 40 publications
5
71
4
3
Order By: Relevance
“…Accordingly, central systolic pressure and augmentation index were higher in nonadherent patients. Similar to other reports, drug class did not appear to have any important impact on the adherence and nonadherence rates in patients with TRH; this result contrasts with findings in mild to moderate hypertension8, 9 (Figure 1). …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Accordingly, central systolic pressure and augmentation index were higher in nonadherent patients. Similar to other reports, drug class did not appear to have any important impact on the adherence and nonadherence rates in patients with TRH; this result contrasts with findings in mild to moderate hypertension8, 9 (Figure 1). …”
Section: Discussionsupporting
confidence: 86%
“…Several outcome research studies found that nonadherence to antihypertensive agents significantly increased cardiac and cerebrovascular risk 5, 6, 7. Furthermore, the choice of prescribed drug class affects adherence rates of antihypertensive therapies 8, 9. In patients with treatment‐resistant hypertension (TRH), who are treated on average with 5 to 6 antihypertensive agents, fixed‐dose combinations mitigate the problem of taking multiple pills per day, but in addition to the antihypertensive agents, these comorbid patients generally require additional cardioprotective drugs (eg, statins, antidiabetic agents) 1, 10…”
Section: Introductionmentioning
confidence: 99%
“…In other study this information confirmed that lower adherence was associated with more prescribed medications [10], especially in users of diuretics and beta blockers, rarely in users of angiotensin -converting enzyme inhibitors (ACEI) and angiotensin II receptor blockers (ARB) [11], which was promoted by…”
Section: Discussionmentioning
confidence: 55%
“…Через год остаются на терапии диуретиками 20,8 % пациентов, через 4 года -16,4 %, что в два раза ниже, чем на терапии бета-блокаторами. Эти данные подтвеждаются и результатами метаанализа I. Kronish с соавторами, в котором было продемонстрировано, что наихудшая приверженность у диуретиков и бета-бло-каторов [33]. В то же время рандомизированные иссле-дования говорят о том, что тиазидоподобные диуретки, наоборот, имеют хорошую переносимость и высокую приверженность.…”
Section: огляд / Reviewunclassified